Developing the ‘OCRAT’ Progressive Web Application (PWAs) for assessing ovarian cancer risk strategies - Nguyen, Hoang Bach; Tran, Doan Tu; Nguyen, Vu Quoc Huy (Tạp chí Y Dược Huế, 2024)
Introduction: Early prediction of ovarian cancer has not been given much attention, the application of combined models in clinical practice is not widespread, and the calculation of these models is still difficult due to the complexity and multiple variables. we have developed a PWA (Progressive Web Apps) application called OCRAT (Ovarian Cancer Risk Assessment Tools - Ovarian Cancer Risk Assessment Tools) with the goal of simplifying the calculation, contributing to increasing the ability to apply these models in clinical practice, teaching, and scientific research. Materials and methods: We used Progressive Web App (PWA) to build the app including four distinct models ROMA, CPH-I, RMI 4, and ADNEX. Results: The app called OCRAT composes 3 main functions: ROMA&CPH-I, RMI 4, and ADNEX can install and run properly in any operating system. The app was officially announced at the Vietnam National Conference of Obstetrics & Gynecology 2023. Conclusions: This application has been widely introduced to specialized obstetricians and gynecologists and has received positive feedback due to the application’s convenience, accuracy, and ease of access